Animal to human translational paradigms relevant for approach avoidance conflict decision making. (September 2017) - Kirlic, Namik; Young, Jared; Aupperle, Robin L.
Abstract: Avoidance behavior in clinical anxiety disorders is often a decision made in response to approach-avoidance conflict, resulting in a sacrifice of potential rewards to avoid potential negative affective consequences. Animal research has a long history of relying on paradigms related to approach-avoidance conflict to model anxiety-relevant behavior. This approach includes punishment-based conflict, exploratory, and social interaction tasks. There has been a recent surge of interest in the translation of paradigms from animal to human, in efforts to increase generalization of findings and support the development of more effective mental health treatments. This article briefly reviews animal tests related to approach-avoidance conflict and results from lesion and pharmacologic studies utilizing these tests. We then provide a description of translational human paradigms that have been developed to tap into related constructs, summarizing behavioral and neuroimaging findings. Similarities and differences in findings from analogous animal and human paradigms are discussed. Lastly, we highlight opportunities for future research and paradigm development that will support the clinical utility of this translational work. Highlights: Analogous rodent and human behavioral tasks support translational research. Approach-avoidance conflict is highly relevant for avoidance and decision-making. Translational human approach-avoidance conflict tasks have recently been developed. Translational human research has corroborated and extended animal research. Future translational behavioral research could enhance understanding of anxiety.